Intrinsic and extrinsic factors that influence ovarian environment and efficiency of reproduction in cattle - Baruselli, Pietro Sampaio; Batista, Emiliana Oliveira Santana; Vieira, Lais Mendes; Sales, José Nélio de Sousa; Gimenes, Lindsay Unno [UNESP]; Ferreira, Roberta Machado (Colegio Brasileiro de Reproducao Animal - CBRA, 2017)
The emergent concepts on ovary environment, reproductive physiology and the development of pharmacology are constantly supporting the advance of assisted reproduction. Within the last years, the biotechnics related to the synchronization of follicular development and the manipulation of bovine estrus cycle have progressed rapidly and consistently. The combined use of timed-artificial insemination (TAI), superovulation (SOV), ovum pick up (OPU), in vitro embryo production (IVEP) and timed-embryo transfer (TET) has a great potential to improve reproductive outcomes and disseminate selected genetics, diminishing the interval of generations and improving herds genetic gain. However, several factors can potentially affect the efficiency of these procedures. The knowledge of the particularities of the genetic groups, follicular growth manipulation, follicular population predictors, and metabolic and environmental aspects that interfere with ovarian environment and, consequently, oocyte quantity and quality is crucial to optimize the reproductive programs. This review aims to elucidate some factors that affect the ovarian environment and must be well known in order to improve the efficiency of reproduction in cattle.
Keywords: AMH; Follicle; Genetic group; Heat stress; Insulin; Oocyte